PEMBENTUKAN AKHLAQUL KARIMAH BERBASIS PEMADUAN SEKOLAH DAN PESANTREN - Asrori, Achmad (Analisis: Jurnal Studi Keislaman, 2014)
This paper attempts  to formulate  good moral formation through the integration  pattern  of superior value of Ordinary School and Boarding  School. This  attempt   is  particularly  relevant  to  the current  situation  where the  Indonesian nation  is facing serious challenges,  especially  in the context  of good moral community development.  The strategy  offered rests on the development  of psycho-Sufi  (Sufism)  which is integrated  in the  two  forms  of activities, namely: (a) the day-to-day activities- by examples, spontaneous  activities,  reprimands, environmental  conditioning, and routine activities; and (b) programed activities- by the preparation of lesson plan loaded with good moral values. The steps to be taken such as: (1) identification of basic competencies  of a subjects including its measurement  indicators;  (2) identification of good moral values, combined with science and technology; (3) selection  of appropriate  teaching  materials;  (4) implementation of the learning activities  supported by tools / media / sources; (5) evaluation to assess the success of the learning process of science (instructional effect) and good moral values as nurturant  effects (side effects)  in the learning activities.  The Formulation  of the interaction   models  between  teachers  and  students  to  prepare good moral graduates are conducted through: (a) positioning  the interaction  between teachers and students within the framework of preparing them to emulate  and to follow the footsteps  of his teachers. (b) positioning  the learner as Talib al-’ilm (the seekers of knowledge)  in  the  school;.  and (c)  creating  an  educational interaction  atmosphere  in the school.